MANAJEMEN LABA DAN PERUBAHAN TARIF PPH UNDANG-UNDANG NO. 36 TAHUN 2008 (Studi Empiris pada Perusahaan BUMN dan Non-BUMN di BEI Tahun 2007-2010 ) - Sri Suranta; Bandi Bandi; Eko Arif Sudaryono (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2016)
Income Tax Act current in Indonesia is marked by the issuance of Law No. 36 of 2008. These laws regulate some fundamental changes in the calculation of corporate income tax for companies in Indonesia. One of the most fundamental changes is the change in the rate used in calculating the tax for the company, which was originally using progressive rates (maximum rate of 30%) to 28 % in 2009, and will be 25 % in 2010. This study is a descriptive study with a quantitative approach. Based on predefined criteria sample, then the total number of samples studied is 193 samples. The variables of study include the discretionary accrual earnings management use with Jones model are current asset changes, cash changes, changes in current liabilities, changes in short-term debt, and changes to the income tax paid. Methods of data collection with secondary data are obtained through documentation of ICMD years 2007-2010. Analysis use parametric statistical with t -test and the non-parametric with Wilcoxon test. The results showed all the company showed indications of earnings management before and after the tax law No. 36 in 2008. State-owned companies showed no difference in earnings management prior to the year after adoption of Law No. 36 in 2008, meanwhile the non-SOE companies show indication of earnings management. Keywords: The issuance of Law No. 36 of 2008, income tax, earnings management, discretionary current accruals.